New Diphosphine Ligands Containing Ethyleneglycol and Amino Alcohol Spacers for the Rhodium-Catalyzed Carbonylation of Methanol - Thomas, Christophe M.; Mafua, Roger; Therrien, Bruno; Rusanov, Eduard; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 2002)
The new diphosphine ligands Ph2PC6H4C(O)X(CH2)2OC(O)C6H4PPh2 (1: X=NH; 2: X=NPh; 3: X=O) and Ph2PC6H4C(O)O(CH2)2O(CH2)2OC(O)C6H4PPh2 (5) as well as the monophosphine ligand Ph2PC6H4C(O)X(CH2)2OH (4) have been prepared from 2-diphenylphosphinobenzoic acid and the corresponding amino alcohols or diols. Coordination of the diphosphine ligands to rhodium, iridium, and platinum resulted in the formation of the square-planar complexes [(PP)Rh(CO)Cl] (6: PP=1; 7: PP=2; 8: PP=3), [(PP)Rh(CO)Cl]2 (9: PP=5), [(P-P)Ir(cod)Cl] (10: PP=1; 11: PP=2; 12: PP=3), [(PP)Ir(CO)Cl] (13: PP=1; 14: PP=2; 15: PP=3), and [(PP)PtI2] (18: PP=2). In all complexes, the diphosphine ligands are trans coordinated to the metal center, thanks to the large spacer groups, which allow the two phosphorus atoms to occupy opposite positions in the square-planar coordination geometry. The trans coordination is demonstrated unambiguously by the single-crystal X-ray structure analysis of complex 18. In the case of the diphosphine ligand 5, the spacer group is so large that dinuclear complexes with ligand 5 in bridging positions are formed, maintaining the trans coordination of the P atoms on each metal center, as shown by the crystal structure analysis of 9. The monophosphine ligand 4 reacts with [{Ir(cod)Cl}2] (cod=cyclooctadiene) to give the simple derivative [(4)Ir(cod)Cl] (16) which is converted into the carbonyl complex [(4)Ir(CO)2Cl] (17) with carbon monoxide. The crystal structure analysis of 16 also reveals a square-planar coordination geometry in which the phosphine ligand occupies a position cis with respect to the chloro ligand. The diphosphine ligands 1, 2, 3, and 5 have been tested as cocatalysts in combination with the catalyst precursors [{Rh(CO)2Cl}2] and [{Ir(cod)Cl}2] or [H2IrCl6] for the carbonylation of methanol at 170 °C and 22 bar CO. The best results (TON 800 after 15 min) are obtained for the combination 2/[{Rh(CO)2Cl}2]. After the catalytic reaction, complex 7 is identified in the reaction mixture and can be isolated; it is active for further runs without loss of catalytic activity.
Keywords: amino alcohols; homogeneous catalysis; phosphane ligands; rhodium